Sentralisasi Siaran Televisi dan Pengingkaran Hak Masyarakat Atas Informasi - Ade Armando (Jurnal InterAct, 2014)
Due to the centralistic broadcasting system, current commercial television stations cannot play a role to empower communities in the process of democratization at the local level.   On one hand, the commercial stations that broadcast nationally in Jakarta tend to show Indonesia through a Jakarta perspective. On the other hand, local news footages are predominantly negative events that have no relevance and insignificant to the problems of local communities. It then becomes a serious problem given the ongoing decentralization in Indonesia today. At the local level, people also need a means of social control so that political power does not concentrate in the hands of authorities in Jakarta. The concern is that there would be misused benefits that are contrary to the welfare of society. The Broadcasting Act 2002 was an effort to break these centralizing tendencies, which mandates the implementation of networked television broadcast system.